Job satisfaction of construction professionals: case study in eastern Mexico - Solís-Carcaño, Rómel G.; González-Fajardo, José A.; Castillo-Gallegos, Rommy A. (Revista de la Construcción. Journal of Construction, 2015)
Work is an intense and demanding activity; in order to perform productive tasks well, it is necessary to have both, disposition and capacity, as well as appropriate working conditions. Job satisfaction surveys are a widely accepted way to know the level of fulfillment of these variables from the employee’s perspective; job satisfaction has been developed as a concept related to a positive emotional state resulting from the individual´s appraisal of his/her job or job experiences. A wide variety of studies have been conducted to measure job satisfaction in the construction industry, most of which have focused on laborers. The aim of this study was to explore job satisfaction levels of construction professionals working for construction firms in Eastern Mexico. The instrument used to measure job satisfaction was the Minnesota Satisfaction Questionnaire, developed for different types of trades and professions, including engineering. The model on which this instrument is based takes into account job satisfaction comprising twenty variables; the methodology may be applied in different geographic contexts. In this case, the results showed that, in general, the group of professionals under study was dissatisfied; while the sub-groups of executives and supervisors expressed satisfaction. The method for the analysis of results can be functional in other regions in the world. It was concluded therefore that there is much room for improvement in the construction industry to professionalize human resource management, and provide better job environments for the employees.